2012
DOI: 10.1589/jpts.24.813
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Preoperative Evaluation of Rotator Cuff Injuries on the Prediction of the Convalescence Period

Abstract: Abstract.[Purpose] The purpose of this study was to assess the effectiveness of preoperative evaluation results of rotator cuff injuries. [Subjects and Methods] On the day of surgery, data were collected from 19 patients (12 males and 7 females; mean age 62.7 ± 6.6 years) diagnosed with rotator cuff injuries. The evaluation included assessment of range of motion, muscle strength, and rotator cuff function with regard to the postoperative period until active elevation of the shoulder joint, and the pain thresho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…Clinicians and researchers are confounded by the various outcome measures used for the assessment of injury of the upper limbs 5 , 6 , 7 ) . In addition to rating the clinimetric properties of a questionnaire, the selection of a particular questionnaire is dependents on its purpose and applicability.…”
Section: Discussionmentioning
confidence: 99%
“…Clinicians and researchers are confounded by the various outcome measures used for the assessment of injury of the upper limbs 5 , 6 , 7 ) . In addition to rating the clinimetric properties of a questionnaire, the selection of a particular questionnaire is dependents on its purpose and applicability.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with rotator cuff tears are initially treated conservatively; however, surgical intervention is employed when the initial treatment fails. Postoperative physical therapy is also administered to allow the patients to regain their range of shoulder motion 1 , 2 , 3 ) . In the study by Koo et al 4 ) , it was suggested that early passive motion after arthroscopic rotator cuff repair (ARCR) had beneficial effects on the range of motion and pain relief; similarly, in the report by Düzgün et al 6 ) , it was demonstrated that an accelerated post-ARCR rehabilitation protocol prevented the negative effects of immobilization and supported rapid reintegration into activities of daily living.…”
Section: Introductionmentioning
confidence: 99%
“…Recent retrospective studies have shown that patients who received no formal physical therapy or limited physical therapy regained their range of motion and demonstrated no significant restrictions at 1 year after surgery. However, no studies have yet evaluated functional outcomes and daily-living activities within the first six months following surgery 5 , 6 , 7 , 8 , 9 ) . This study evaluated short-term patient outcomes after arthroscopic rotator cuff repair multiple times at 1 week intervals using a postoperative rehabilitation protocol with early passive motion.…”
Section: Introductionmentioning
confidence: 99%